Laser thermal therapy for epilepsy surgery: current standing and future perspectives. (15th July 2020) - Zemmar, Ajmal; Nelson, Bradley J.; Neimat, Joseph S.
Abstract: More than 130-year ago, Sir Victor Horsley delivered a landmark address to the British Medical Association, in which he described successful localization and resection of an epileptogenic focus resulting in seizure freedom for the patient. Several important steps in epilepsy surgery have been achieved since, including resection techniques such as anterior temporal lobectomy and selective amygdalohippocampectomy, both resulting in 70–80% seizure freedom and distinct differences in neuropsychological outcomes. The most recent addition to techniques for epilepsy surgery is minimally invasive thermal therapy. Significant advances in imaging technology and thermal ablation have opened a novel avenue for epilepsy treatment, permitting surgical intervention with seizure-freedom rates approaching the success of traditional methods but with reduced invasiveness, blood loss and duration of postoperative hospital stay. Here, we review recent advances on stereotactic ablation techniques focused on epilepsy surgery. Finally, we present emerging navigation techniques, which allow a higher degree of freedom. The described technologies render precise navigation of the ablation probe to avoid critical structures along the trajectory path and open novel pathways to further minimize invasiveness and improve safety and efficacy. Improve safety and efficacy.